Dynamics in digital information systems : festschrift volume in honour of Prof. M. Bavakutty - Amudhavalli, A.; Chandrakumar, V.; Bavakutty, M. (New Delhi : Ess Ess Publications, 2008)
Contributed articles containing recent developments in library and information science in India
Includes bibliographical references and index
Keywords: Digital libraries -- India; Library information networks -- India